Board Attributes and Audit Quality of Quoted Financial Firms in Nigeria - Abdullahi, Sani Rufai; Elaigwu, Moses; Ibrahim, Ademu Stephen (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The reliability of accounting information, which heavily depends on the quality of financial Audit report, is crucial for users. The board of directors, appointed to protect shareholders' interests, is legally empowered to oversee management and ensure high-quality audits of their operations. In this context, this study investigates the relationship between board attributes and audit quality among publicly traded financial firms in Nigeria from 2016 to 2022. The specific objectives are to analyze how board size, board independence and female directors on board relate to the engagement of Big Four audit firms, which represents audit quality. A sample size of 45 firms were selected through purposive sampling. Binary logistic regression was used to analyse the effect of board attributes on audit quality of listed financial firms in Nigeria. The results indicated that board size and significantly and positively affect audit quality, while board independence and female directors on the board have an insignificant effect on audit quality. The study recommends larger board sizes, more independent non-executive directors and more female directors to ensure high-quality audits in the Nigerian financial firms.